THE EFFECT OF ROLE PLAYING METHODS ON THE EMOTIONAL SOCIAL DEVELOPMENT OF ELEMENTARY SCHOOL CHILDREN - Miftahul Hayatun; Nurhasanah; Siti Istiningsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
During the learning process, it was found that students did not treat their friends kindly; they did not answer questions from friends and teachers seriously. Moreover, the students were also less motivated in learning and did not keep the learning atmosphere conducive. These conditions were caused by differences in the students’ social-emotional development. Thus, teachers needed to find a method to foster the students' social-emotional development; one of which was the role-playing method. The purpose of this study was to find the effect of the role-playing method on the students’ social-emotional development at grade III group 2 Ambalawi in the academic year 2020/2021. The design of this study was a Nonequivalent Control Group Design. The population of this study was all grade III elementary school students of group 2 Ambalawi in the academic year 2020/2021. The samples were selected by purposive sampling, in which the students of grade III SDN 1 Rite served as the experimental class and the students of grade III SDN Inpres 2 Rite served as the control class. The hypotheses were tested by using the independent sample t-test, and the data were analyzed using SPSS version 16.0. The results of data analysis showed that the value of t-count was 9.917 and t-table was 2.042, meaning that t-count ≥ t-table. By looking at the Sig. (2-tailed) value of 0.000 ≤ 0.05 at the significant level of 5% with df 30, it was revealed that Ha was accepted. This implied that the role-playing method provided a significant influence on the students’ social-emotional development at grade III group 2 Ambalawi in the academic year 2020/2021.